CROSS-SECTORAL COOPERATION IN CULTURAL HERITAGE: CURRENT STATE, CHALLENGES AND PERSPECTIVES IN SERBIA (Heritage, 2026)
The aim of this paper is to analyze cross-sectoral cooperation in the field of cultural heritage in order to assess its current state, identify the main challenges and make proposals for its improvement. The methodological framework of the research is based on a desk analysis of the existing regulatory and institutional framework, the results of an online survey conducted between 30 September and 18 October 2024. and interview with representatives of stakeholders. The findings indicate that cross-sectoral cooperation is not adequately integrated into the regulatory and institutional system of the protection of cultural heritage and mostly takes place at ad hoc or project level. The main challenges in establishing collaborative management in the field of cultural heritage are the lack of interest of stakeholders involved in the protection and presentation of cultural heritage, the limited financial resources, the lack of developed and tested collaborative management models that can be applied on the practical level and conflict in cultural heritage values among different stakeholders. Cross-sectoral cooperation is most evident in activities related to the presentation and interpretation of cultural heritage, manifestation and tourist promotion while it is largely absent in participatory decision-making processes, participatory budgeting and urban planning. An effective cultural heritage policy requires cross-sectoral cooperation that is systematically structured, defined in regulatory terms and based on long-term planning, with the aim of integrating cultural heritage into sustainable development processes. Particular attention should be paid to the mapping and increased involvement of relevant stakeholders from the profit and exploring their potential in decision-making, management and funding cultural heritage, while cultural policies should stimulate cross-sectoral cooperation.
Keywords: Cultural heritage, Cross-sectoral cooperation, Serbia, Cultural policy, Collaborative management, Institutional environment, Governance, Participatory decision-making, Protection, Conservation, Appropriate use, Stakeholders.